A First‐in‐Patient, Multicenter, Double‐Blind, 2‐Arm, Placebo‐Controlled, Randomized Safety and Tolerability Study of a Novel Oral Drug Candidate, CTP‐499, in Chronic Kidney Disease. Issue 4 (11th February 2016) - Sabounjian, LuAnn; Graham, Philip; Wu, Lijun; Braman, Virginia; Cheng, Changfu; Liu, Julie; Shipley, James; Neutel, Joel; Dao, Michael
Abstract: The prevalence of chronic kidney disease (CKD) related to type 2 diabetes is increasing worldwide. In addition to standard of care, treatment with anti‐inflammatory and antifibrotic agents such as CTP‐499, a novel oral, multisubtype selective inhibitor of phosphodiesterases, may be important in CKD treatment. A phase 1b randomized, double‐blind, placebo‐controlled clinical trial of CTP‐499 in CKD patients (25 active, 8 placebo) with an estimated glomerular filtration rate of 30–59 mL/min/1.73 m 2 was conducted to assess safety and tolerability. Secondary outcomes included pharmacokinetics and exploratory effects on inflammatory and hematology markers. Patients received 600 mg CTP‐499 or matching placebo tablets orally once daily for 2 weeks, then twice daily for 2 additional weeks. CTP‐499 was well tolerated with no serious or severe adverse events, or adverse events leading to discontinuation. CTP‐499 was rapidly absorbed and produced acceptable interpatient variability. Of the 5 metabolites (M1–M5), M5 was the most abundant in plasma and urine. Exposure to CTP‐499 and metabolites was higher in CKD patients than previously reported in healthy volunteers. No statistically significant differences were detected between the CTP‐499‐ and placebo‐treated groups for any of the biomarkers tested. This study provides data supporting further evaluation of CTP‐499 in CKD patients.